Post a New Question

Math

posted by on .

(√ 10 +3)(√ 10 - 3)

When I multiply the √ 10's what would it come out to be? That's what throws me off >_<

  • Math - ,

    ( a + b ) ( a - b ) = a ^ 2 - b ^ 2



    [ sqrt ( 10 ) + 3 ] [ sqrt ( 10 ) - 3 ] =

    sqrt ( 10 ) ^ 2 - 3 ^ 2 =

    10 - 9 = 1




    If your expression mean :

    sqrt [ ( 10 ) + 3 ] sqrt [ ( 10 ) - 3 ]

    then

    sqrt [ ( 10 ) + 3 ] sqrt [ ( 10 ) - 3 ] =

    sqrt ( 13 ) sqrt ( 7 ) =

    sqrt ( 13 * 7 ) = sqrt ( 91 )

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question